2018
DOI: 10.1038/s41559-018-0525-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfers can date the tree of life

Abstract: Biodiversity has always been predominantly microbial and the scarcity of fossils from Bacteria, Archaea and microbial Eukaryotes has prevented a comprehensive dating of the tree of life. Here we show that patterns of lateral gene transfer deduced from the analysis of modern genomes encode a novel and abundant source of information about the temporal coexistence of lineages throughout the history of life. We use state-of-the-art species tree aware phylogenetic methods to reconstruct the history of thousands of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 42 publications
1
64
0
Order By: Relevance
“…With the increasing availability of molecular data, phylogenetic trees generated from different genes are often recognized to have conflicting branching patterns (Maddison 1997;Nichols 2001;Pamilo and Nei 1988). Davin et al (2018) suggested that different genetic markers could yield conflicting estimates of the species phylogeny. In recent years, genome-scale sequence data have become increasingly available in phylogenetic studies for understanding the evolutionary histories of species (Liu et al 2015).…”
Section: Conflicts Between Non-reproductive Genes (F1 and Igs) And Thmentioning
confidence: 99%
“…With the increasing availability of molecular data, phylogenetic trees generated from different genes are often recognized to have conflicting branching patterns (Maddison 1997;Nichols 2001;Pamilo and Nei 1988). Davin et al (2018) suggested that different genetic markers could yield conflicting estimates of the species phylogeny. In recent years, genome-scale sequence data have become increasingly available in phylogenetic studies for understanding the evolutionary histories of species (Liu et al 2015).…”
Section: Conflicts Between Non-reproductive Genes (F1 and Igs) And Thmentioning
confidence: 99%
“…Various attempts in this direction are currently being made but this is clearly a challenging undertaking due to large computational demands of using complex evolutionary models on big datasets. Yet, the further improvement of models of evolution and phylogenetic algorithms (including molecular dating approaches such as recently employed by Wolfe andFournier 2018 andDavín et al 2018) in combination with ever increasing computational resources will certainly help to further refine the tree of life and get a better supported location of the root.…”
Section: An Expanded Microbial Treementioning
confidence: 99%
“…For a given set of donor and recipient species, where only the latter has a known fossil record, since the transfer of genetic material must post-date the divergence of the donor lineage, the earliest fossil evidence of the recipient also provides evidence for the minimum age of the donor (dos Reis, 2018). This approach has been used to date divergence times among microbial lineages, most of which lack a substantive fossil record (Davín et al, 2018;Wolfe and Fournier, 2018a;Magnabosco et al, 2018;Gruen et al, 2019). This approach has the potential for constraining parasite evolution, as HGTs have been documented between some hosts and their parasites, including several parasitic plant groups (Molina et al, 2014;Kado and Innan, 2018).…”
Section: Prospects For Understanding the Coevolutionary Dynamics Of Hmentioning
confidence: 99%